FORMATION AND DEVELOPMENT OF THE ASEAN POLITICAL-SECURITY COMMUNITY (Вісник: Міжнародні відносини, 2025)
Background. The Association of Southeast Asian Nations (ASEAN) is a regional association of 10 countries, namely: Indonesia, Malaysia, Singapore, the Philippines, Thailand, Brunei, Vietnam, Laos, Myanmar and Cambodia. This Association has managed not only to ensure peace and stability in Southeast Asia (SEA), but also to play a leading role in establishing and promoting a security architecture in the Asia-Pacific region (APAC) through the promotion of cooperative security. In this regard, there is a need to analyze the foundations of ASEAN's functioning and its security policy, which is implemented through the ASEAN Political-Security Community, the key structure where all ASEAN political and security activities converge. However, the question arises as to the principles of this Political-Security Community, its creation, development and prospects for further functioning in the security environment of the Asia-Pacific region.Methods. The following methods were used in the research: problem-chronological and comparative analysis.Results. The normative legal documents of the Association of Southeast Asian Nations (ASEAN), such as the Bali Declarations, the ASEAN Charter and the Political-Security Community Blueprints, have created the foundation for the functioning and development of the ASEAN Political-Security Community (APSC). These documents provide a regulatory framework for cooperative security and define its principles in ASEAN's activities.The ASEAN Political-Security Community has demonstrated the ability to adapt to changes in the regional and global security environment. This includes expanding its role from the regional to the global level, especially in the area of cross-border challenges.Conclusions. The ASEAN Political-Security Community continues to develop in accordance with the ASEAN Political-Security Community Blueprint for 2016-2025. This process envisages long-term and strengthened ASEAN political and security cooperation, which will have an impact on the security of the wider Asia-Pacific region in the medium and long term perspectives.
Keywords: ASEAN, ASEAN Political-Security Community, cooperative security, Asia-Pacific